2006
DOI: 10.1158/0008-5472.can-05-3158
|View full text |Cite
|
Sign up to set email alerts
|

A Gene Expression Signature that Can Predict Green Tea Exposure and Chemopreventive Efficacy of Lung Cancer in Mice

Abstract: Green tea has been shown to be a potent chemopreventive agent against lung tumorigenesis in animal models. Previously, we found that treatment of A/J mice with either green tea (0.6% in water)

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 22 publications
2
32
0
Order By: Relevance
“…The genes that were affected by treatment with green tea and Polyphenon E in a similar carcinogenesis model have been reported by Lu et al (46). Direct targets of EGCG action identified by different methods in other systems have also been reported (47,48).…”
Section: Discussionsupporting
confidence: 64%
“…The genes that were affected by treatment with green tea and Polyphenon E in a similar carcinogenesis model have been reported by Lu et al (46). Direct targets of EGCG action identified by different methods in other systems have also been reported (47,48).…”
Section: Discussionsupporting
confidence: 64%
“…Lu et al [20] recently analyzed the gene expression changes caused by the administration of green tea or PPE to chemically-induced mouse model for lung tumorigenesis. They found that 88 genes that were differentially expressed in tumors (from the normal tissues) were reversed by the treatment and suggested that these genes may be used as markers for tea exposure.…”
Section: Lung Tumorigenesismentioning
confidence: 99%
“…Finally, we will discuss the relevance of these results in the prevention of human cancer based on human epidemiological and interventions studies. This topic has been covered by previous reviews (Yang and Wang, 1993;Bushman, 1998;Yang et al, 2002;Hou et al, 2004;Lambert et al, 2005;Clark and You, 2006;Khan et al, 2006;Lu et al, 2006b;Sun et al, 2006b;Sun et al, 2006a;Wu and Yu, 2006;Yang et al, 2006a;Yang et al, 2006b). Because of the citation limitations, we will cite the key reviews instead of some of the original articles.…”
Section: Introductionmentioning
confidence: 99%